Trends in Annual Temperature Changes for the Current and Projected Period in the Kingdom of Saudi Arabia for the Period from (2016 -2100 AD) Using Geographic Information Systems - alharpi, mona (Journal of King Abdulaziz University: Environmental Design Sciences, 2025)
Climate change, particularly shifts in temperature, has become one of the most critical areas of focus in recent climatological studies due to its profound impact on life on Earth. This study aimed to examine trends in annual temperature changes, both current and projected, in the Kingdom of Saudi Arabia for the period from 2016 to 2100, across three intervals: the reference period, mid-century, and end-century. These projections were based on two emissions scenarios: the moderate emissions scenario (RCP4.5) and the high emissions scenario (RCP8.5). The study employed a descriptive and analytical approach, utilizing climate change data from the outputs of the RICCAR initiative. Additionally, a cartographic method was applied through the use of Geographic Information Systems (GIS) to process, classify, and analyse the study's data. Among the key findings was a general trend of increasing annual temperatures in Saudi Arabia under both moderate and high emissions scenarios across all study periods. Theregions most vulnerable to significant rises in annual temperature include the Eastern Province and parts of the northern and north western regions (Medina, Tabuk, and Al-Jawf), as well as portions of central Saudi Arabia (Riyadh, Qassim, and Hail). Furthermore, the high emissions scenario (RCP8.5) projected that by the end of the century (2081–2100), annual temperature increases in some regions of Saudi Arabia will not be less than 3.20°C, reaching up to 4.67°C in certain areas.